Tissue paper laminate

A laminate of a porous film and thin paper addresses the issue of thermal deformation in disposable warming products, achieving low thermal deformation rates and reducing petroleum plastic use, thereby enhancing product usability and minimizing environmental impact.

JP2025054300APending Publication Date: 2025-04-08KOHJIN FILM & CHEM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023163342
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Disposable warming products face issues with thermal deformation during heat sealing, leading to warping and wrinkles, which affect usability and appearance. Additionally, the use of petroleum-derived plastics contributes to environmental concerns such as global warming and oil depletion.

Method used

A laminate comprising a porous film made from a stretched resin containing polyolefin and inorganic filler, combined with thin paper, which suppresses thermal deformation during heat sealing. This laminate has a thickness of 180 μm or less and meets specific thermal deformation rate criteria at various heat sealing temperatures.

Benefits of technology

The laminate achieves a low thermal deformation rate of approximately 0% in both longitudinal and width directions under high heat sealing temperatures, preventing warping and wrinkles. This improves the appearance and usability of disposable warmers while reducing the use of petroleum-derived plastics, thus minimizing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054300000001
    Figure 2025054300000001
Patent Text Reader

Abstract

To provide a laminate exhibiting moisture permeability, that is preferable for hyperthermia medical application such as specifically, a disposable body warmer or the like, the laminate exhibiting a low heat deformation ratio during heat sealing, and capable of contributing to petroleum resource saving and global warming prevention by CO2 emission reduction.SOLUTION: A laminate exhibiting moisture permeability between a porous film and tissue paper having a basis weight of 40 g / m2 or less, has a thickness of 180 μm or less, and the following conditions (1) and (2) are simultaneously satisfied when two sheets of the laminates are overlapped with each other in such a manner that porous films are brought into contact with each other, and are heat-sealed. (1) Under a heat-sealing condition of a temperature of 140°C, a pressure of 0.5 MPa, and a time of 0.5 seconds, a thermal deformation ratio in a longitudinal direction and a thermal deformation ratio in a width direction in a heat sealing region each are 1.0% or less. (2) Under the heat-sealing condition of a temperature of 160°C, a pressure of 0.5 MPa, and a time of 0.5 seconds, a thermal deformation ratio in a longitudinal direction and a thermal deformation ratio in a width direction in the heat sealing region each are 1.0% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a moisture-permeable laminate, and more specifically to a laminate of a porous film and tissue paper that can be used for thermal medical purposes, such as the pouch of a disposable body warmer or the base material of a thermal patch. [Background technology]

[0002] A method is widely known in which an inorganic filler is blended with a polyolefin resin such as a polyethylene resin or a polypropylene resin, the resulting mixture is formed into a sheet, and then stretched to form a breathable film. The breathable film is used for various disposable body warmers in the field of hyperthermia treatment, for example, by laminating a nonwoven fabric on the breathable film and using the laminate in the form of a bag for a disposable body warmer.

[0003] In the manufacture of the disposable warmer, when the breathable film / nonwoven fabric laminate and the heat generating agent are packaged in a bag making machine, the heat-melting resin used in the breathable film melts and solidifies by the heat sealing in the bag making machine, so that the heat generating agent inside the disposable warmer can be packaged without leaking. However, due to differences in the thermal deformation rates of the breathable film and the nonwoven fabric, warping and wrinkles can occur in the heat sealed area, which not only impairs the aesthetic appearance but also makes the disposable warmer uncomfortable to the touch when in use, which can lead to discomfort for the user.

[0004] In recent years, against the backdrop of environmental issues such as future petroleum depletion and global warming, there has been growing interest in using paper instead of petroleum-derived resins, which leads to a reduction in environmental impact through reduced CO2 emissions. For example, tissue paper generally has a basis weight of 40 g / m 2 This refers to the thin paper listed below, and is widely used as wrapping paper for shirts, shoes, etc., and as inner wrap. To date, products using tissue paper have weighed approximately 19.53 to 24.41 g / m 2A food wrap product has been proposed which is made of tissue paper, at least a portion of which is coated or impregnated with a biodegradable composition, and the biodegradable composition comprises two types of thermoplastic biodegradable polymers characterized by their glass transition temperatures (Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4809215 specification Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, issues with disposable hand warmers include deterioration of the aesthetics and usability of the hand warmer itself due to deformation of the heat-sealed parts of the pouch material. Furthermore, in recent years, there has been a demand to reduce the use of petroleum-derived plastics in order to reduce CO2 emissions, which have an impact on global warming. And because both the breathable film and nonwoven fabric used in disposable warmer bags are made from plastic, there is a demand for materials that can reduce the amount of plastic used, even if only slightly. Although the food wrap product proposed in the aforementioned Patent Document 1 uses tissue paper as a base material, which can lead to reduced environmental impact, there is no discussion whatsoever about the thermal deformation of the wrap product, and no mention is made of the wrap product being applicable to thermal medical applications such as hand warmers, etc. Furthermore, no proposals have been made to date for breathable sheets or the like using tissue paper for thermal medical applications.

[0007] The present invention has been made in consideration of the above problems, and aims to provide a moisture-permeable laminate that not only has a low thermal deformation rate during heat sealing, which leads to the elimination of defects such as wrinkles and warping caused by thermal deformation, but also contributes to the prevention of global warming by saving petroleum resources and reducing CO2 emissions, and is particularly suitable for thermal medical applications such as disposable body warmers. [Means for solving the problem]

[0008] The present inventors have surprisingly found that by replacing the nonwoven fabric with tissue paper in a conventional laminate of breathable film and nonwoven fabric, deformation such as warping and wrinkles during heat sealing between film parts can be suppressed. In particular, by forming a laminate by combining a specific porous film with tissue paper, it has been found that thermal deformation such as heat shrinkage can be suppressed in both the longitudinal and transverse directions under a relatively high and wide heat sealing temperature condition of 140 to 160 ° C. In addition, the use of tissue paper as a substitute for nonwoven fabric can reduce the amount of petroleum-derived plastic used, which in turn leads to the suppression of CO2 emissions, and the present invention has been completed.

[0009] That is, the present invention provides the following. [1] Porous film with a basis weight of 40g / m 2 A laminate having moisture permeability with the following thin paper, The thickness of the laminate is 180 μm or less, and when two sheets of the laminate are overlapped with their porous film surfaces in contact with each other and heat sealed, the laminate satisfies both of the following conditions (1) and (2): (1) When the heat sealing conditions are a temperature of 140°C, a pressure of 0.5 MPa, and a time of 0.5 seconds, the thermal deformation rate in the longitudinal direction and the width direction at the heat-sealed area is both 1.0% or less. (2) When the heat sealing conditions are a temperature of 160°C, a pressure of 0.5 MPa, and a time of 0.5 seconds, the thermal deformation rate in the longitudinal direction and the width direction at the heat-sealed area are both 1.0% or less. [2] The laminate according to [1], wherein the porous film is a stretched resin film containing a polyolefin resin and an inorganic filler, the polyolefin resin is contained in an amount of 30 to 70 parts by mass relative to 100 parts by mass of the porous film, and the inorganic filler is contained in an amount of 30 to 70 parts by mass relative to 100 parts by mass of the porous film. [3] The polyolefin resin is a mixture of linear low-density polyethylene and an ethylene-α-olefin copolymer, The laminate according to [2], wherein the inorganic filler is calcium carbonate. [4] The thin paper has a basis weight of 25 g / m 2 Preferably less than 20 g / m 2 The laminate according to [1], [5] The laminate described in [4], wherein the tissue paper contains pulp fibers, water-absorbing and water-retentive starch, and optionally additives, and the pulp fibers contain 10% or less of crimped fibers. [6] The laminate described in [1] further comprises an adhesive layer between the porous film and the tissue paper, the adhesive layer comprising an air-permeable area where no adhesive is present and a non-air-permeable area where adhesive is present. [7] The laminate according to any one of [1] to [6], wherein the laminate has an air permeability of 8000 sec / 100 cc or more as measured in accordance with JIS P8117. [8] The laminate according to [7], which is used for thermomedical purposes. Effect of the Invention

[0010] According to the present invention, a porous film and a basis weight of 40 g / m 2By using the laminate having moisture permeability with the following thin paper, it is possible to provide a laminate in which the thermal deformation rate at the heat-sealed portion is low and warping or wrinkling is unlikely to occur even when the porous film surfaces are heat-sealed together. In particular, by using a laminate in which a porous film made of a stretched resin film containing a specific resin and an inorganic filler is laminated with a specific thin paper, it is possible to realize a low thermal deformation rate of almost 0% in both the longitudinal direction and the width direction under a relatively high and wide heat-sealing temperature condition of 140 to 160 ° C., and it is possible to provide a laminate in which warping or wrinkling does not occur at the heat-sealed portion. Therefore, according to the present invention, when a disposable warmer bag or the like is manufactured from the laminate by heat sealing, it is possible to prevent deterioration in appearance and usability due to deformation such as warping or wrinkling at the heat-sealed portion. In addition, when manufacturing a bag, it is also effective in preventing deterioration in the running performance of the manufacturing machine due to warping or wrinkling caused by heat sealing. Furthermore, according to the present invention, by using tissue paper as an alternative material to nonwoven fabric, the amount of petroleum-derived plastic materials used can be reduced compared to conventional methods, thereby reducing the environmental burden. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described.

[0012] [Laminate] The present invention relates to a moisture-permeable laminate comprising a porous film and a basis weight of 40 g / m 2 The following laminates with tissue paper are applicable. The configuration and characteristics of the laminate of the present invention will be described in detail below.

[0013] <Porous film> The porous film used in the laminate of the present invention may be, for example, a stretched resin film containing a polyolefin resin and an inorganic filler. By stretching the film containing the resin and the filler, voids are generated around the filler, making the film porous.

[0014] (Polyolefin resin) The polyolefin resin used in the present invention is a resin produced from a polyethylene-based resin made from raw materials obtained from fossil fuels such as petroleum, or from renewable resources other than fossil fuels, in particular from bioethanol derived from plants such as sugar cane, and is a resin having at least an olefin component (such as α-olefins such as ethylene, propylene, butene-1, pentene-1, hexene-1,4-methyl-pentene-1, heptene-1, and octene-1) as a monomer component.

[0015] Examples of the polyolefin resin include polyethylene resins such as low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, and ethylene-α-olefin copolymers (e.g., ethylene-propylene copolymers), as well as polypropylene resins (polypropylene, propylene-α-olefin copolymers), polybutene resins (polybutene-1, etc.), and poly-4-methylpentene-1. Examples of the polyolefin resin include ethylene-unsaturated carboxylic acid copolymers such as ethylene-acrylic acid copolymers and ethylene-methacrylic acid copolymers, ethylene-(meth)acrylic acid ester copolymers such as ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers and ethylene-methyl methacrylate copolymers, ethylene-acetic acid copolymers, and the like. Copolymers of olefin component monomers with other copolymerizable monomers, such as vinyl copolymers and ethylene-vinyl alcohol copolymers, can also be used. In this specification, (meth)acrylic acid refers to acrylic acid and methacrylic acid. In the present invention, the polyolefin resins can be used alone or in combination of two or more.

[0016] Among these, the polyolefin resin used in the present invention is preferably a polyethylene resin, more preferably at least one selected from the group consisting of low-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymer, and ethylene-methyl methacrylate copolymer, and particularly preferably a mixture of linear low-density polyethylene and ethylene-α-olefin copolymer. In the above mixture, the mixing ratio of the linear low-density polyethylene and the ethylene-α-olefin copolymer is not particularly limited, but for example, the content of the ethylene-α-olefin copolymer is preferably 5 to 90 parts by mass, more preferably 10 to 50 parts by mass, per 100 parts by mass of the linear low-density polyethylene. If the content of the ethylene-α-olefin copolymer is less than 5 parts by mass, the processability such as heat seal strength may be impaired, and if it exceeds 90 parts by mass, the tear strength may be reduced.

[0017] The content of the polyolefin resin in the porous film can be, for example, 30 to 70 parts by mass, or, for example, 35 to 65 parts by mass, or 40 to 60 parts by mass, based on 100 parts by mass of the porous film. It should be noted that if the content of the polyolefin resin is less than 30 parts by mass, the processability such as heat seal strength may be impaired. On the other hand, if it exceeds 70 parts by mass, the content of the inorganic filler in the porous film is reduced, which may make it difficult to form voids, and since the amount of the polyolefin resin is large, it is difficult to contribute to reducing CO2 emissions. As described above, the polyolefin resins may be used alone or in combination of two or more kinds, and the petroleum-derived polyolefin resins and plant-derived polyolefin resins may be used alone or in combination of two or more kinds, as long as they are within the above-mentioned content ranges.

[0018] (Inorganic filler) The inorganic filler used in the present invention plays a role in making the film porous by generating voids around the inorganic filler through the stretching process as described above. Examples of such inorganic fillers include talc, silica, stone powder, zeolite, alumina, aluminum powder, and iron powder, as well as carbonates such as calcium carbonate, magnesium carbonate, magnesium-calcium carbonate, and barium carbonate, sulfates such as magnesium sulfate and barium sulfate, metal oxides such as zinc oxide, titanium oxide, and magnesium oxide, metal hydroxides such as aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, calcium hydroxide, and barium hydroxide, and metal hydrates such as magnesium oxide-nickel oxide hydrate and magnesium oxide-zinc oxide hydrate. In the present invention, the above inorganic fillers can be used alone or in combination of two or more.

[0019] The inorganic filler used in the present invention is not particularly limited with respect to its shape, and various shapes such as a plate shape or a particulate shape can be adopted, but from the viewpoint of void formation by the stretching process, a particulate shape is preferred.

[0020] Of these, calcium carbonate and barium sulfate can be preferably used in the present invention, and calcium carbonate, particularly particulate calcium carbonate, can be preferably used.

[0021] The average particle size of the inorganic filler is not particularly limited, but may be, for example, 0.1 to 20.0 μm, or 0.5 to 10.0 μm. If the average particle size of the inorganic filler is less than 0.1 μm, there is a risk of secondary aggregation of the inorganic filler causing poor dispersion, and if it exceeds 10.0 μm, it should be noted that film breakage or poor appearance may occur. The average particle size of the inorganic filler can be a value calculated from the results of measuring the specific surface area by an air permeability method in accordance with JIS M 8511.

[0022] The content of the inorganic filler in the porous film can be, for example, 30 to 70 parts by mass, or, for example, 35 to 65 parts by mass, or, alternatively, 40 to 60 parts by mass, relative to 100 parts by mass of the porous film. It should be noted that if the content of the inorganic filler is less than 30 parts by mass, voids may be difficult to form, and if it exceeds 70 parts by mass, poor dispersion of the inorganic filler and a decrease in tear strength may easily occur.

[0023] (Additives) The porous film according to the present invention may further contain various additives such as colorants, antioxidants, antioxidants, UV absorbers, flame retardants and stabilizers, as necessary, within the range that does not impair the effects of the present invention.

[0024] (Method of manufacturing porous film) An example of a method for producing a porous film is shown below. First, the polyolefin resin and inorganic filler, and other additives as necessary, are mixed in a mixer, and then melt-kneaded in a suitable kneader. Specifically, the mixture is mixed using a mixer such as a Henschel mixer, a super mixer, a Banbury mixer, or a tumbler mixer, and then melt-kneaded at 170 to 240 ° C., preferably 190 to 220 ° C., using a single- or twin-screw extruder equipped with a T-die or the like, and cooled and solidified to obtain a sheet-like material. At that time, from the viewpoint of further improving the homogeneity of the mixed raw materials and the dispersibility of the inorganic filler, it is preferable to melt-knead the mixed raw materials thoroughly using a twin-screw extruder, then cool and solidify to prepare a compound that is once pelletized, and then melt-knead the pelletized compound again using a single- or twin-screw extruder equipped with a T-die or the like, and cool and solidify to obtain a sheet-like material. In this way, by repeating the melt-kneading process and the cooling and solidifying process two or more times using an extruder, the homogeneity of the mixture of the polyolefin resin and the inorganic filler and the dispersibility of the inorganic filler are improved, and it becomes easier to suppress the unevenness of the thickness and the variation of the air permeability of the obtained porous film. In addition, in the present invention, it is also possible to mix and use recycled products such as trimmings generated during film production and non-standard products within a range that does not interfere with the purpose of the present invention.

[0025] The obtained sheet-like material is stretched 2 to 6 times in each of the uniaxial and biaxial directions using a known method such as a roll method or a tenter method, causing interfacial peeling between the polyolefin resin and the inorganic filler, thereby generating voids around the inorganic filler, and a porous film is obtained. The stretching ratio can have a large effect on the physical properties of the porous film, and if it is less than 2 times, the interfacial peeling between the polyolefin resin and the inorganic filler is insufficient, and satisfactory breathability may not be obtained. On the other hand, if the stretching ratio exceeds 7 times, the tensile elongation of the film may decrease. Considering the above reasons, the stretching ratio is preferably 2 to 7 times, more preferably 3 to 6 times. The stretching temperature is preferably in the range of room temperature to the softening point of the polyethylene resin. After stretching, if necessary, a heat setting treatment may be carried out to stabilize the shape of the obtained film.

[0026] The thickness of the porous film can be 20 to 160 μm, for example, 30 to 130 μm, or for example, 40 to 100 μm. If the thickness of the porous film is less than 20 μm, edge tearing (a phenomenon in which the film tears at the boundary between the heat-sealed portion and the non-heat-sealed portion) is likely to occur when forming a laminate described later and producing a bag such as a disposable warmer by heat sealing. Also, if the thickness exceeds 160 μm, the heat sealability is deteriorated, and there is a risk that sealing failure is likely to occur.

[0027] <Tissue paper> Thin paper generally has a basis weight of 40 g / m 2 It refers to the thin and soft paper described below, which is widely used in shoe toenails, cushioning materials, wrapping paper, packaging materials, etc. Since tissue paper has very high breathability and is comparable to the breathability of nonwoven fabric, it can be used as a substitute for nonwoven fabric in the moisture-permeable laminate of the present invention.

[0028] The tissue paper preferably has a basis weight of 30 g / m 2 Less than or equal to 25 g / m 2 More preferably, 20 g / m or less 2 The following can be used: 2 If it exceeds this limit, the basis weight of the tissue paper will be exceeded, and not only will its properties of being thin, soft, and highly breathable be lost, but there is also concern that the benefits of reducing environmental impact will be diminished. The lower limit of the basis weight of tissue paper is determined automatically based on the thickness that can be manufactured and the durability of the product. For example, it is 10 g / m 2 or more than 15g / m 2 The above and so on are possible.

[0029] The above-mentioned tissue paper may contain, for example, pulp fibers, water-absorbing and water-retentive starch, and additives as necessary, and the pulp fibers may contain 10% or less of crimped fibers. Examples of the additives include fillers such as minerals, colorants, surfactants, and other additives commonly used in the art.

[0030] The tissue paper may be colored paper, or original tissue paper may be produced by printing and used.

[0031] (adhesive layer) The laminate of the present invention may further include an adhesive layer between the porous film and the tissue paper. The adhesive layer is preferably a layer consisting of a breathable area where no adhesive is present and a non-breathable area where adhesive is present. The adhesive layer having such an embodiment can form a moisture-permeable laminate without impairing the high breathability of the porous film or the tissue paper.

[0032] (Method of manufacturing laminate) The method for producing the laminate of the porous film and tissue paper is not particularly limited. For example, any known method such as dry lamination or hot melt adhesion may be used as long as the adhesion method is capable of adjusting the air permeability.

[0033] To form an adhesive layer consisting of the above-mentioned breathable areas where no adhesive is present and non-breathable areas where adhesive is present, for example, when applying the adhesive, the adhesive can be applied in an application pattern such that the non-applied areas of the adhesive are discontinuous, and the porous film and tissue paper can be laminated together. This coating pattern is not particularly limited as long as the non-coated areas of adhesive are discontinuous, but taking into consideration the peel strength of the laminate and the efficiency of adhesive coating, a lattice pattern can be selected in which the coated areas form regular lattice lines.

[0034] (Laminate thickness) The laminate of the present invention has a thickness of 180 μm or less, for example 150 μm or less, and If the thickness of the laminate exceeds 180 μm, the moisture permeability (breathability) of the entire laminate may be impaired, and when used in products such as disposable warmers, the laminate may become hard and uncomfortable to the touch. The lower limit of the thickness of the laminate can be appropriately set in consideration of the strength of the laminate, and can be, for example, 30 μm or more, or 50 μm or more.

[0035] (Air permeability of laminate) The laminate of the present invention has a Gurley air permeability of 645.16 mm 2 It is preferable that the air permeability, measured according to the number of seconds required for 100 cc of air to pass through an area of ​​the sheet (unit: sec / 100 cc), is, for example, 5,000 sec / 100 cc or more, 6,000 sec / 100 cc or more, 7,000 sec / 100 cc or more, or even 8,000 sec / 100 cc or more.

[0036] (Thermal deformation rate of laminate) By having the above-mentioned configuration, the laminate of the present invention becomes a laminate in which the thermal deformation rate of the heat-sealed portion is low and warping or wrinkling is unlikely to occur even when the porous film surfaces are heat-sealed together. Specifically, when two laminates are overlapped with their porous film surfaces in contact with each other and heat sealed, the following conditions (1) and (2) are both satisfied. (1) When the heat sealing conditions are a temperature of 140°C, a pressure of 0.5 MPa, and a time of 0.5 seconds, the thermal deformation rate in the longitudinal direction and the width direction at the heat-sealed portion are both 1.0% or less, and preferably 0.5% or less. (2) When the heat sealing conditions are a temperature of 160°C, a pressure of 0.5 MPa, and a time of 0.5 seconds, the thermal deformation rate in the longitudinal direction and the width direction at the heat-sealed portion are both 1.0% or less, and preferably 0.5% or less. The procedure for measuring the dimensional change before and after heat sealing was carried out in accordance with the JIS Z 1707 standard for heat shrinkage. Specifically, before heat sealing, the length of the heat-sealed portion of the sample in the longitudinal or transverse direction is measured (basically 100.0 mm). After heat sealing under the above conditions, the length of the heat-sealed portion is measured in the longitudinal or transverse direction. The thermal deformation rate is then calculated from the amount of dimensional change before and after heat sealing. Note that, because thermal deformation includes thermal contraction and thermal expansion, the thermal deformation rate is expressed as an absolute value.

[0037] The laminate of the present invention can be used for thermomedical applications, such as bags for disposable body warmers; building material applications, such as roof waterproofing materials; packaging material applications, such as desiccants, moisture-proofing agents, oxygen absorbers, and freshness-preserving packaging; sanitary material applications, such as disposable diapers and sanitary napkins; and material applications, such as battery separators. Among these, it is preferable for it to be used for thermomedical applications. EXAMPLES

[0038] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples and comparative examples.

[0039] In the examples and comparative examples, the types of raw materials, tissue paper, and nonwoven fabric used in the production of the porous film constituting the laminate, and the evaluation methods for the performance of the porous film and laminate are shown below. [Porous film (raw material)] A: Linear low-density polyethylene (density 0.919 g / cm 3 , MFR(190℃)2.0g / 10min) B: Linear low-density polyethylene (density 0.920 g / cm 3 , MFR(190℃) 1.9g / 10min) C: Ethylene-α-olefin copolymer (density 0.885 g / cm 3 , MFR(190℃) 3.6g / 10min) D: Ethylene-α-olefin copolymer (density 0.940 g / cm 3 , MFR(190℃)2.0g / 10min) E: Calcium carbonate [Thin paper, non-woven fabric] F: Tissue paper G:PET-SB nonwoven fabric H:PET-SL non-woven fabric I: Ny-SB nonwoven fabric J:PP-SMS nonwoven fabric K:PP-SB non-woven fabric [Adhesive layer] Adhesive made mainly of polyester resin, polyisocyanate hardener, and carboxylic acid ester solvent

[0040] 1.Thickness The thicknesses of the laminates of the examples and comparative examples and the porous films used in the laminates were measured according to JIS K Measurement was performed according to 7130. Specifically, a test piece 150 mm long and 100 mm wide was cut from the produced laminate or porous film, and measurements were taken at 10 points (n=10) in the width direction, and the average value was used as the thickness.

[0041] 2. Air permeability The air permeability of the laminates of the examples and comparative examples was measured according to JIS P 8117 (Gurley air permeability: 645.16 mm 2 The area was measured in seconds for 100cc of air to pass through (unit: sec / 100cc).

[0042] 3. Thermal deformation rate of heat-sealed area The thermal deformation rate was measured according to the following procedure. The procedure for measuring the dimensional change before and after heat sealing was in accordance with the JIS Z 1707 standard for thermal shrinkage. <Heat sealing procedure> From the laminates of the Examples and Comparative Examples, roughly square test pieces 100 mm long and 100 mm wide were cut, folded in half in the longitudinal or width direction so that the porous film surface of the test piece was on the inside (test piece after folding: length 50 mm × width 100 mm, or length 100 mm × width 50 mm), and the porous film surfaces were heat-sealed over the entire surface. The heat-sealing conditions were as follows (1) or (2). (1) Temperature: 140°C, pressure: 0.5MPa, time: 0.5 seconds (2) Temperature: 160°C, pressure: 0.5MPa, time: 0.5 seconds The longitudinal heat sealing and the widthwise heat sealing were carried out separately, and the dimensional change before and after heat sealing was measured (n=2) using the procedure described below. The thermal deformation rate was calculated, and the average value was taken as the measured value. <Measurement procedure for dimensional change> After cutting the roughly rectangular test piece in the above <Heat sealing procedure>, the length of the heat-sealed portion in the longitudinal or transverse direction of the tissue paper side of the test piece was measured before heat sealing (basically 100.0 mm). After folding the sample in half in the longitudinal or transverse direction and heat sealing, the dimensional change in the length of the heat-sealed portion was measured in the longitudinal or transverse direction. The thermal deformation rate (%) was calculated from the measured dimensional change and the dimension before heat sealing (100.0 mm).

[0043] Example 1 Linear low-density polyethylene, ethylene-α-olefin copolymer, and calcium carbonate were mixed in a Henschel mixer according to the composition shown in Table 1, and then melt-kneaded and pelletized in a twin-screw extruder at 200°C. The pellets were then fed into a single-screw extruder equipped with a T-die to produce an unstretched film of 150 to 250 μm. The unstretched film was then stretched in the machine direction (MD) by roll stretching using a longitudinal uniaxial stretching machine at a stretching temperature of 80°C and a stretch ratio of 4.7 times to obtain a porous film of 60.0 μm in thickness. A conventional polyester adhesive was applied to the porous film using a gravure roll in a grid pattern with a center-to-center distance of 1.8 mm in both the vertical and horizontal directions, and then dry laminated with tissue paper to obtain the laminate of Example 1. The thickness of the laminate obtained in Example 1 was 83 μm, and the thermal deformation rate of the heat-sealed portion when the porous film surfaces of the laminate were heat-sealed together under the above heat-sealing condition (1) was 0.0% in both the longitudinal and transverse directions, and the thermal deformation rate under the heat-sealing condition (2) was 0.0% in both the longitudinal and transverse directions. The obtained results are also shown in Table 1.

[0044] Example 2 In the production of the porous film, the raw materials and compositions were as shown in Table 1, and the stretching ratio was changed to 4.3 times, but a porous film having a thickness of 50 μm was obtained in the same manner as in Example 1. The porous film and tissue paper were dry laminated in the same manner as in Example 1 to obtain the laminate of Example 2. The thickness of the obtained porous film of Example 2 and the thermal deformation rate of the heat-sealed portion when the porous film surfaces of the laminate of Example 2 were heat-sealed under the heat-sealing conditions (1) or (2) were measured according to the above-mentioned procedures. The results are shown in Table 1.

[0045] Comparative Example 1 A 60 μm thick porous film was obtained in the same manner as in Example 1. The tissue paper had a basis weight of 30 g / m 2 A laminate of Comparative Example 1 was obtained in the same manner as in Example 1, except that the PET-SB nonwoven fabric was changed to the above-mentioned PET-SB nonwoven fabric. The thickness of the obtained porous film of Comparative Example 1 and the thermal deformation rate of the heat-sealed portion when the porous film surfaces of the laminate of Comparative Example 1 were heat-sealed under the heat-sealing conditions (1) or (2) were measured according to the above procedures. The results are shown in Table 1.

[0046] Comparative Example 2 A porous film having a thickness of 70 μm was obtained in the same manner as in Example 1, except that the stretching ratio was changed to 4.2 times. 2 A laminate of Comparative Example 2 was obtained in the same manner as in Example 1, except that the PET-SL nonwoven fabric was changed to the above-mentioned PET-SL nonwoven fabric. The thickness of the obtained porous film of Comparative Example 2 and the thermal deformation rate of the heat-sealed portion when the porous film surfaces of the laminate of Comparative Example 2 were heat-sealed under the heat-sealing conditions (1) or (2) were measured according to the above procedures. The results are shown in Table 1.

[0047] Comparative Example 3 A porous film having a thickness of 60 μm was obtained in the same manner as in Example 1, except that the stretching ratio was changed to 4.8 times. 2A laminate of Comparative Example 3 was obtained in the same manner as in Example 1, except that the Ny-SB nonwoven fabric was changed to Ny-SB. The thickness of the obtained porous film of Comparative Example 3 and the thermal deformation rate of the heat-sealed portion when the porous film surfaces of the laminate of Comparative Example 3 were heat-sealed under the heat-sealing conditions (1) or (2) were measured according to the above procedures. The results are shown in Table 1.

[0048] Comparative Example 4 A porous film having a thickness of 60 μm was obtained in the same manner as in Example 1, except that the stretching ratio was changed to 4.5 times. 2 A laminate of Comparative Example 4 was obtained in the same manner as in Example 1, except that the PP-SMS nonwoven fabric was changed to the above-mentioned PP-SMS nonwoven fabric. The thickness of the obtained porous film of Comparative Example 4 and the thermal deformation rate of the heat-sealed portion when the porous film surfaces of the laminate of Comparative Example 4 were heat-sealed under the heat-sealing conditions (1) or (2) were measured according to the above procedures. The results are shown in Table 1.

[0049] Comparative Example 5 A porous film having a thickness of 60 μm was obtained in the same manner as in Example 1, except that the stretching ratio was changed to 4.6 times. 2 A laminate of Comparative Example 5 was obtained in the same manner as in Example 1, except that the PP-SB nonwoven fabric was changed to the above-mentioned PP-SB nonwoven fabric. The thickness of the obtained porous film of Comparative Example 5 and the thermal deformation rate of the heat-sealed portion when the porous film surfaces of the laminate of Comparative Example 5 were heat-sealed under heat-sealing conditions (1) or (2) were measured according to the above procedures. The results are shown in Table 1.

[0050] Comparative Example 6 A porous film having a thickness of 70 μm was obtained in the same manner as in Example 1, except that the composition of the porous film was changed to that shown in Table 1 and the stretching ratio was changed to 4.6 times. 2 A laminate of Comparative Example 6 was obtained in the same manner as in Example 1, except that the PP-SB nonwoven fabric was changed to the above-mentioned PP-SB nonwoven fabric. The thickness of the obtained porous film of Comparative Example 6 and the thermal deformation rate of the heat-sealed portion when the porous film surfaces of the laminate of Comparative Example 6 were heat-sealed under heat-sealing conditions (1) or (2) were measured according to the above procedures. The results are shown in Table 1.

[0051] [Table 1]

[0052] As shown in Table 1, the laminates of Examples 1 and 2, which use tissue paper, hardly experience any thermal deformation at the heat-sealed portion, compared to the laminates using the nonwoven fabric used in the Comparative Example. The results suggest that it is possible to obtain quality that is free of defects (both 0.0%) and has a beautiful appearance. It is also suggested that, when bags or the like are manufactured using the laminates of Examples 1 and 2, running problems such as meandering caused by deformation of the heat-sealed portion during bag manufacturing and packaging can be prevented. In addition, by using tissue paper instead of nonwoven fabric, the laminate of the present invention can reduce the thickness of the laminate itself, which can also contribute to reducing CO2 emissions. Therefore, when used primarily for thermal medical applications, it can make a significant contribution to reducing the environmental load.

Claims

1. Porous film and basis weight 40 g / m 2 A laminate having moisture permeability with the following thin paper, The thickness of the laminate is 180 μm or less, and when two sheets of the laminate are overlapped with the porous film surfaces in contact with each other and heat-sealed, the laminate satisfies both of the following conditions (1) and (2). (1) When the heat sealing conditions are a temperature of 140° C., a pressure of 0.5 MPa, and a time of 0.5 seconds, the thermal deformation rate in the longitudinal direction and the thermal deformation rate in the width direction at the heat-sealed portion are both 1.0% or less. (2) When the heat sealing conditions are a temperature of 160° C., a pressure of 0.5 MPa, and a time of 0.5 seconds, the thermal deformation rate in the longitudinal direction and the thermal deformation rate in the width direction at the heat-sealed portion are both 1.0% or less.

2. The laminate according to claim 1, wherein the porous film is a stretched resin film containing a polyolefin resin and an inorganic filler, the polyolefin resin is contained in an amount of 30 to 70 parts by mass per 100 parts by mass of the porous film, and the inorganic filler is contained in an amount of 30 to 70 parts by mass per 100 parts by mass of the porous film.

3. The polyolefin resin is a mixture of linear low-density polyethylene and an ethylene-α-olefin copolymer, The laminate according to claim 2 , wherein the inorganic filler is calcium carbonate.

4. The thin paper has a basis weight of 25 g / m 2 Preferably, the basis weight is 20 g / m or less. 2 2. The laminate of claim 1, wherein:

5. 5. The laminate according to claim 4, wherein the tissue paper comprises pulp fibers, water-absorbing and water-retentive starch, and, if necessary, additives, and the pulp fibers contain 10% or less of crimped fibers.

6. The laminate of claim 1, further comprising an adhesive layer between the porous film and the tissue paper, the adhesive layer having an air-permeable area where no adhesive is present and a non-air-permeable area where adhesive is present.

7. The laminate according to claim 1 , wherein the laminate has an air permeability of 8000 sec / 100 cc or more as measured in accordance with JIS P8117.

8. The laminate according to claim 7, which is used for thermomedical purposes.

Citation Information

Patent Citations

  • JP1973009215A